Rancang Bangun Aplikasi Pengadaan Barang Pada Bulog Subdivre Surabaya Utara - Rahmawati, Novita; Widodo, Arifin Puji; Sutanto, Teguh (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
BULOG is a state-owned company engaged in food logistics. Bulog has Sub division regional (Subdivre) which has the task to procure goods domestically to meet the supply of grain / rice in the warehouse. Currently, Subdivre Surabaya Utara has had an application in the procurement of goods, but there are obstacles in the application used. There is no limit on the business partners contract and no warning notification if the data has exceeded the contract. Consequently, the business partners can send the goods exceeding the contract which has been determined. In addition, there is no protection that the business partners can not create a new contract with the same type of sack when the old contract with the same type of sack has not been fulfilled.Based above problems, the authors create an application of procurement that contains the selection of business partners, PJB making, selection of quality, a check on the business partners contract, history of business partnership, SPP making and wanprestasi. It can guarantee the quality of the application of procurement in Subdivre Surabaya Utara to conform to the standard operating procedures (SOP) which has been determined.The application created can produce the required reports which are report of procurement, GD1M report, receipt of goods recapitulation, report on the history of Business Partners, the selection result of Business Partners, sale and purchase agreement, quality report and wanprestasi. The system created can provide detailed information as well as provide more accurate and faster data and report in the procurement of goods (rice / grain). Keywords: Implementation Application, Information, Procurement of goods.